Sociocultural portrait of a female sexton in 1919‒1941 (according to archives of the Urals) - Andrei Pecherin (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
In accordance with a tradition established in the Russian Orthodox Church, the participation of women in the liturgical service is very limited. In monasteries, women could sing and read on the kliros, in parish life they could serve as prosphora bakers. In the 20th century, the woman’s role in the church started to change. Social movement towards a fuller participation of women in church life, having originated in aristocratic circles of the capital cities, by 1918 has increased to such an extent, that it came to be refl ected in the statute of the Local Council, according to which a woman under certain circumstances could be admitted to serve in the altar as a psalm-reader. Mass departure of the clergy with A. Kolchak’s army in 1919 and the closure of monasteries made easier the implementation of this statute in the Urals. At fi rst, active and young monastery novices and widows were called to the service of sextons. The medium age of a female sexton was ca. 30. Afterwards, many women who were close to the priest and made up the framework of the parish demonstrated courage and determination in defending churches and affi rming the Orthodox faith, which was the reason for arrests and exile. Despite the repressions, the instute of female sextons existed in the church during the entire Soviet period and has survived in a somewhat altered shape up to the present time. Now, a female sexton is not a rarity in many female monasteries, they can be met in rural parishes as well. Thus, in the 20th century, a new type of the female service appeared in the Russian Orthodox Church, i.e. being a sexton.